2006
DOI: 10.1007/s10926-006-9043-2
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity disorders in the workplace: Costs and outcomes beyond the first return to work

Abstract: A substantial proportion of workers with CTD or work-related back pain experience injury-related absences after their first return to work. Focusing on the first return to work is misleading for both injury groups, but even more so for CTD, as they appear to be even more susceptible to multiple spells of work absence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 10 publications
5
67
0
2
Order By: Relevance
“…In this study, therate of symptom existence in any part of theupper body is found to be 61.1%. This result is in line with previous research by which the prevalence is reported between 27% and 63% (13). In a study carried by Abledu et al, the density of upper body area symptoms within last 12 months is found to be 83.5% (14,15), while Bhanderi reported frequency as 72.2% (6,14).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, therate of symptom existence in any part of theupper body is found to be 61.1%. This result is in line with previous research by which the prevalence is reported between 27% and 63% (13). In a study carried by Abledu et al, the density of upper body area symptoms within last 12 months is found to be 83.5% (14,15), while Bhanderi reported frequency as 72.2% (6,14).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, RTW after SA due to MSD is frequently marked by multiple spells of absenteeism and cannot be viewed as one RTW event (17). The purpose of this study was to (i) examine RTW after a workrelated MSD using traditional time-to-event analysis, (ii) identify RTW trajectories among injured workers with work-related MSD, (iii) examine the associations between different MSD and RTW trajectories, and (iv) compare the results obtained from the various methods.…”
Section: Return-to-work Trajectories After Musculoskeletal Disordersmentioning
confidence: 99%
“…Repetitive movements necessitated by the use of input devices has been linked to the growing issue of repetitive strain injury (RSI) [41]. Studies show that RSI costs US employers more than $6.5 billion annually [42]. This highlights the benefits which may be offered by a universal design, desirable as both a mainstream and assistive product.…”
Section: Introductionmentioning
confidence: 99%